Factors Affecting Being Alcoholic Among College Students on Their Academic Performance: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to explore the relationship between alcoholism among college students andtheir academic performance. The results suggest that being an alcoholic user can have anegative impact on academic performance, leading to lower grades, increased absences, anddifficulty focusing. It is important for college students to provide resources and support forstudents struggling with alcohol use to improve their academic success and overall well-being.The results of the survey showed that the majority of the respondents are between the ages of18 and 27, and 48% are male and 52% are female. The research created a guide to give thempossible factors affecting being alcoholic among college student and their academicperformance. Thus, the study recommends that college students focus on their studiesinstead of drinking alcoholic beverages.Based on our survey, we discovered that drinking alcohol makes them unwell, which has animpact on their academic performance. Students in college drink not just to relieve stress ordeal with problems but also to have fun or celebrate. Our suggestions are well-accepted bymany college students who want to stop consuming alcohol.
Keywords: Hotel and Restaurant Management